Whose pharaohs? : archaeology, museums, and Egyptian national identity from Napoleon to World War I - Reid, Donald M. (University of California Press, 2002)
Cover -- Contents -- List of Illustrations -- Acknowledgments -- Note on Transliteration, Translation, and Dates -- Introduction -- PART ONE: IMPERIAL AND NATIONAL PRELUDES, 17981882 -- 1. Rediscovering Ancient Egypt: Champollion and al-Tahtawi -- 2. From Explorer to Cooks Tourist -- 3. Egyptology under Ismail: Mariette, al-Tahtawi, and Brugsch, 18501882 -- PART TWO: IMPERIAL HIGH NOON, NATIONALIST DAWN, 18821914 -- 4. Cromer and the Classics: Ideological Uses of the Greco-Roman Past -- 5. Egyptology in the Age of Maspero and Ahmad Kamal -- 6. Islamic Art, Archaeology, and Orientalism: The Comit233; and Ali Bahgat -- 7. Modern Sons of the Pharaohs? Marcus Simaika and the Coptic Past -- Conclusion -- Appendix: Supplementary Tables -- Notes -- Select Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.